Local structural disorder and charge inhomogeneity induced relaxor ferroelectricity in CuCrO2 - Tripathy A.; Dey K.; Sahu S.R.; Bano N.; Kumar V.; Garg P.; Singh S.; Kumar V.; Zimmermann M.V.; Deshpande U.; Sathe V.G.; Shukla D.K. (My University, 2025)
Investigation of Pb-free relaxor ferroelectric materials and analysis of their physical properties in relation to their local structure have emerged as captivating area of research. The CuCrO2, a centrosymmetric delafossite, exhibits a diffused ferroelectric phase transition with a broad dielectric relaxation maxima at Tm≈453 K and a Burn's temperature at TB≈468 K. It does not exhibit a clear signature of temperature-induced structural phase transition, however, anomalous changes in crystallographic parameters across TB have been observed. Raman spectroscopy results also underline anomalies in the distinct vibrational modes below TB, depicting association of local structural changes with ferroelectric ordering. Here, we report the origin of high-temperature relaxor ferroelectricity in CuCrO2, through detailed structural and local structural analysis. A real-space local structural study by x-ray pair distribution function (PDF) analysis, as a function of temperature, establishes a clear picture of temperature-induced structural instabilities from local to intermediate length scales. PDF analysis through the box car fitting demonstrate the presence of local structural disorder below TB at a length scale of ≈20 Å. X-ray photoelectron spectroscopy (XPS) investigations revealed mixed oxidation states for Cu, implying the existence of charge inhomogeneity in the compound. Our findings reveal that both local structural disorder and charge inhomogeneity are responsible for appearance of relaxor ferroelectric behavior in CuCrO2. © 2024 American Physical Society.